Аномалії насіння Ginkgo biloba L. - Sinitsyna, L.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2000)
The results of ivestigation of Ginkgo biloba L. in the State Nikita Botanical Gardens, N.N. Grishko National Botanical Gardens and O.V. Fomin Botanical Gardens collections have been stated. The anomalies of seeds with the following increasing of their quantity have been found.